ANALISIS APLIKASI AKAD BAY’ PADA PROJECT BASED SUKUK (PBS) DI INDONESIA: Analysis of the Application of the Bay’ Contract in Project Based Sukuk (PBS) in Indonesia - Kurniawan, Taufiq; Ab Rahman, Asmak (Jurnal Syariah, 2020)
Islamic economic development is a task incumbent upon a good Muslim community. Indonesia has, in recent years, accelerated its economic development -especially in the area of infrastructure development- thereby requiring additional funding sources to aid this development. Thus, the government has issued Project Based Sukuk (PBS), which aims to finance the development of the country’s infrastructure. PBS is a Shariah-based financing instrument that is an alternative for Muslim communities which are interested in building a country’s economy without elements of ribā. This instrument has a main contract in the form of ijārah and supporting contracts, one of which is al-bay‘. However, the application of these contracts can only be said to be valid from a Sharā‘ perspective if all rules and conditions are throughly fulfilled. This study focuses on analyzing the application of the al-bay‘ contract on PBS. It uses a data collection method by interview and review of literature, which was then analyzed inductively to draw conclusions from the specific to the general. The study found that the majority application of the al-bay‘ contract to PBS is in line with the principles of Shariah, although there are still some issues still to be rectified.